Clinical pharmacology of bispecific antibody constructs. (March 2015) - Rathi, Chetan; Meibohm, Bernd; Korth‐Bradley, Joan; Mager, Donald; Meibohm, Bernd; Zhou, Hong Hui
Abstract The confluence of rapid scientific advancements especially in protein engineering and recombinant technology, unmet medical needs, and commercial incentives have led to the development of the next generation of therapeutic proteins. Bispecific antibody constructs are one of the novel strategies that is being pursued, combining the ability to bind simultaneously to two distinct targets and the advantages of purpose‐designed and optimized antibody‐based scaffolds. Their pharmacokinetic and pharmacodynamic properties, including their immunogenic potential, are closely related to their structural features and ability to interact with disposition mechanisms of immunoglobulin molecules. Catumaxomab and blinatumomab are bispecific constructs that are approved for clinical use and have provided clinical pharmacology data for this novel class of therapeutics. This knowledgebase on the clinical behavior of bispecific therapeutic proteins is poised to rapidly evolve over the next few years with many development programs having entered the clinical development stage.